DEONTOLOGICAL VS TELEOLOGICAL ETHICS IN MODERN PASTORAL COUNSELING PRACTICE - Apriani Delfita Legrans; Marchella Winda Sirang; Maygresye Natalia Sambouw; Ivane Dear Suryani Brek (International Forum of Researchers and Lecturers, 2024)
Abstract: This article discusses two main ethical approaches, namely deontological and teleological in the context of modern pastoral counseling practice. Through conceptual and comparative analysis, this article explores how these two approaches are applied in the moral decisions faced by pastoral counselors when accompanying congregations. This study aims to provide in-depth understanding for pastoral counselors to be able to make ethical decisions that are not only in accordance with moral principles, but also pastorally relevant Keywords: deontological ethics, teleological ethics, pastoral counseling, morality, pastoral theology.